IMPLEMENTASI PERATURAN WALIKOTA SEMARANG NOMOR 20 TAHUN 2010 TENTANG KEBIJAKAN KOTA LAYAK ANAK DENGAN PENDEKATAN KELURAHAN RAMAH ANAK - Setiawan, Muhammad Isnaeni; Suwitri, Sri; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2014)
According to Indonesia national census in 2010, 34,26% of country’s population or 81.415.918 are children (BPS, 210). The definition of children is 0-18 years old citizen having special rights that regulated by international consensus and national regulations. One of these regulations is manifested by the Policy of Proper City for Children with Child-Friendly District Approach which have been implemented by many cities in Indonesia, including Semarang. It is a city development strategy that well-planned, sustainable, and systematically integrates the government’s commitment and sources, citizens, and business sector in fulfilling children’s rights activities. The purpose of this research is to analyze the implementation of Semarang City Major Rules No 20 in the year of 2010 about Proper City for Children with Child-Friendly District Approach and the success-failure aspects including resources, policy characteristic, and communication aspects. These aspects come from several policy implementation models by Van Meter and Van Horn, Merilee S. Grindle, Mazmanian and Sabatier, and also George C. Edward III. The result of this research indicates the implementation of Semarang City Major Rules No. 20/2010 about Proper City for Children with Child-Friendly District Approach has not been implemented as it should be (as it written on the regulation). The resources of policy need to be increased in quantity and quality. The commitment of policy implementation has to be strengthen. And the information of communication aspects has to be cleared. Therefore, it recommended that City Action Plan about this policy should be done immediately.